POE01 Outcome of medication change in patients with refractory epilepsy. Issue 11 (22nd October 2010) - Wong, S H; Smith, D F; Marson, A G
Abstract : Background: Despite the low probability of achieving seizure-freedom in refractory epilepsy patients and clinicians may be inclined to try new or previously untried medications. We assessed the outcome of consecutive medication changes in patients with refractory epilepsy, seen in an adult epilepsy clinic set in a district general hospital. Method: A retrospective review of case notes of patients who failed the first two AEDs. Results: 39 patients were included. Median number of AEDs tried per patient was 5 (range 3–12), over a median (range) follow-up period of 15 years (2–38). In 66/123 treatment episodes improvement was reported at 12 month after introduction of AED but the treatment was later stopped in 25/66 instances because of ineffectiveness or side effects. In 8/35 treatment episodes the drug was continued despite no reported improvement. Conclusions: The majority of treatment changes in patients with refractory epilepsy do not produce sustained benefit. Outcome depends upon duration of follow-up highlighting the difficulty of explaining apparent benefit: treatment or natural history. Our findings have implications for clinical practice and the conduct of controlled clinical trials in patients with refractory epilepsy.